2008
DOI: 10.1007/s10658-008-9282-5
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Rice yellow mottle virus in rice germplasm in Madagascar

Abstract: Salaudeen M.T. (2014): Relative resistance to Rice yellow mottle virus in rice. Plant Protect. Sci., 50: 1-7. We identified sources of Rice yellow mottle virus (RYMV) resistance in rice cultivars. Eight cultivars together with susceptible and resistant controls were evaluated under screenhouse conditions as inoculated and uninoculated treatment in completely randomised design with three replications. Seedlings were inoculated with the virus by sap transmission at two weeks after sowing. Disease incidence and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The highly susceptible reactions of cvs FARO 29 and FARO 44 concur with the previous investigation reported by Abo et al (2002). The partially tolerant cultivars performed better than the susceptible ones because of their strong genetic background to limit the deleterious impacts of the virus (Rakotomalala et al 2008). Earlier, N'Guessan et al (2001 encountered high genetic resistance to RYMV in cv.…”
Section: Discussionmentioning
confidence: 99%
“…The highly susceptible reactions of cvs FARO 29 and FARO 44 concur with the previous investigation reported by Abo et al (2002). The partially tolerant cultivars performed better than the susceptible ones because of their strong genetic background to limit the deleterious impacts of the virus (Rakotomalala et al 2008). Earlier, N'Guessan et al (2001 encountered high genetic resistance to RYMV in cv.…”
Section: Discussionmentioning
confidence: 99%
“…Most cultivated rice varieties have been reported as highly susceptible [14]. Attempts to control rice yellow mottle disease have been mainly directed to breeding for resistance to RYMV [15].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to control rice yellow mottle disease have been mainly directed to breeding for resistance to RYMV [15]. A few sources of resistance to be used in breeding programs were identified [14]- [17]. However, the durability of such resistance was questioned, as resistance-breaking isolates of the virus were shown to occur frequently [18] [19].…”
Section: Introductionmentioning
confidence: 99%
“…Rymv1-2 has only been detected in Gigante and Bekarosaka, which are two cultivars of Asian rice var. indica (Ndjiondjop et al, 2001;Rakotomalala et al, 2008). RYMV2 was recently found in the African rice cultivar Tog7291 (Thiémélé et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These two rice species are affected by Rice yellow mottle virus (RYMV) disease, which is only found on this continent (Kouassi et al, 2005). The screening of cultivars belonging to both cultivated species, by several authors identified two major genes of resistance: RYMV1 and RYMV2, which provide high levels of resistance (Fomba 1988;Ndjiondjop et al, 1999;Rakotomalala et al, 2008;Thiémélé et al, 2010). High resistance is characterised by symptomless plants and the blockage of virus movement inside the plant (Ndjiondjop et al, 2001).…”
Section: Introductionmentioning
confidence: 99%